Fungemia e coroidite por Cryptococcus neoformans relato em portador de SIDA - Parente, Daniel Ramos [UNESP]; Schellini, Silvana Artioli [UNESP]; Marques, Silvio Alencar [UNESP]; Marques, Mariângela Esther Alencar [UNESP] (Conselho Brasileiro de Oftalmologia, 1994)
In this work, we report a case of bilateral choroiditis by C. neoformans occurred in an AIDS patient.

Relatamos um caso de coroidite bilateral por C. neoformans em pacientes portador de SIDA.
Fungemia and choroiditis by Cryptococcus neoformans - case report in an AIDS patient
Keywords: SIDA; Coroidites; Cryptococcus neoformans